Cytoplasmic levels of high mobility group A2 determine survival prognoses in breast cancer patients. Issue 2 (June 2020) - Heilmann, Thorsten; Vondung, Florian; Borzikowsky, Christoph; Krüger, Sandra; Elessawy, Mohamed; Alkatout, Ibrahim; Wenners, Antonia; Bauer, Maret; Klapper, Wolfram; Röcken, Christoph; Maass, Nicolai; Schem, Christian; et al.
Background: High mobility group A proteins are involved in chromatin remodeling, thereby influencing multiple fundamental biological processes. HMGA2 has been linked to oncogenic traits among a variety of malignancies. Objective: To determine the prognostic implications of subcellular distribution patterns of HMGA2 in breast cancer. Methods: Nuclear and cytoplasmic HMGA2 was evaluated in 342 breast cancer specimens and matched with clinico-pathological parameters. Results: Overall and cytoplasmic, but not nuclear, levels of HMGA2 correlated with better survival prognoses in our collective (hazard ratio (HR) 0.34, P = 0.001 and HR 0.34, P < 0.001, respectively). The protective effect of cytoplasmic HMGA2 persisted in the Luminal A and triple negative breast cancer subgroups. Evaluating Luminal A and B subgroups jointly, only cytoplasmic, but not overall or nuclear HMGA2 levels were associated with better survival (HR 0.42, 95% confidence interval 0.21, 0.86, P = 0.017), irrespective of tumor size and node status. The addition of HMGA2 overall and cytoplasmic scores strengthened the prognostic selectivity in a model of conventional breast cancer risk factors. No predictive significance with regard to endocrine or chemoendocrine therapies was observed. Conclusion: Unexpectedly, we found a favorable survival probability upon overall levels of HMGA2 in our breast cancer collective, which was predominantly determined by the presence of HMGA2 in the cytoplasm.